2006
DOI: 10.1139/z06-038
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition-site selection by the toad Melanophryniscus rubriventris in an unpredictable environment in Argentina

Abstract: Oviposition-site selection plays an important role in the reproductive success of amphibians. In unpredictable environments where resources vary within a season, amphibians should select oviposition sites using parameters that can be easily evaluated, or spawn in several ponds to increase offspring survival. Melanophryniscus rubriventris (Vellard, 1947) uses shallow ephemeral ponds in an unpredictable montane-forest environment. During 40 consecutive days, we surveyed potential spawning sites and measured seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
3
28
0
3
Order By: Relevance
“…Wang et al (2007) reported similar results for this species in Ningbo (29850?N, 121838?E, elevation 8 m), Zhejing, eastern China. Also, our results were similar to the spawning site selection of Melanophryniscus rubriventris and Melanophryniscus stelzneri (Goldberg et al 2006;Pereyra et al 2011). The shallow waterbodies may be favorable to promoting oviposition of P. nigromaculata, because spawning behavior of P. nigromaculata differed to B. gargarizans, and eggs are laid without affixing them to the vegetation.…”
Section: Discussionsupporting
confidence: 88%
“…Wang et al (2007) reported similar results for this species in Ningbo (29850?N, 121838?E, elevation 8 m), Zhejing, eastern China. Also, our results were similar to the spawning site selection of Melanophryniscus rubriventris and Melanophryniscus stelzneri (Goldberg et al 2006;Pereyra et al 2011). The shallow waterbodies may be favorable to promoting oviposition of P. nigromaculata, because spawning behavior of P. nigromaculata differed to B. gargarizans, and eggs are laid without affixing them to the vegetation.…”
Section: Discussionsupporting
confidence: 88%
“…Fatores abióticos e bióticos com potencial de influenciar a escolha da fêmea são analisados simultaneamente (e.g., profundidade, propriedades físico-químicas da água, presença e tipo de competidores, predadores). Para inferir se há escolha de locais de postura específicos, os estudos analisam se a distribuição das desovas no ambiente tem associação com alguns desses fatores e se existe preferência ou se determinadas condições são evitadas (e.g., Howard 1978, Seale 1982, Caldwell 1986, Banks & Beebee 1987, Holomuzki 1995, Evans et al 1996, Kam et al 1996, Laurila 1998, Mitchell 2002, Dougherty et al 2005, Ficetola et al 2006, Goldberg et al 2006, Hagman & Shine 2006, Lin & Kam 2008. 2) A segunda abordagem consiste em experimentos controlados em cativeiro ou semi-cativeiro (poças artificiais introduzidas em ambiente natural).…”
Section: Métodos De Estudounclassified
“…Em geral, os estudos têm demonstrado que fêmeas de diversas espécies de anuros de diferentes grupos selecionam sítios de oviposição mais favoráveis à sobrevivência e desenvolvimento de seus ovos e girinos (e.g., Skelly 2001, Binckley & Resetarits-Jr. 2002, 2003, Murphy 2003a, b, Rieger et al 2004, Rudolf & Rödel 2005, Goldberg et al 2006, Halloy 2006, Haramura 2008. Dentre aproximadamente 35 estudos de caso publicados envolvendo 24 espécies, apenas em Rana temporaria Linnaeus, 1758 (Ranidae), a fêmea parece não ser seletiva em relação à presença de predadores de seus girinos (e.g., larvas de insetos, peixes) (Laurila & Aho 1997, Laurila 1998.…”
Section: Compilação Bibliográficaunclassified
See 1 more Smart Citation
“…An analysis of the diversity of temporary ponds used by anurans suggests that not all ponds are equally suitable (Resetarits Jr., 1996). The selection of breeding sites in response to temporary pond characteristics has been frequently documented in several species (Vos and Chardon, 1998;Hazell et al, 2003;Goldberg et al, 2006). Best breeding sites will be those that keep enough water to complete the metamorphosis, and provide resources for tadpoles, i.e.…”
Section: Introductionmentioning
confidence: 99%